Melanotic Neuroectodermal Tumor of Infancy: A Case Report with Review of Literature - Vasundhara Patil; Jeba Nazneen; Pranjal Rai; Ujjwal Agarwal; Abhishek Mahajan (Indian Journal of Medical and Paediatric Oncology)
Melanotic neuroectodermal tumors of infancy are rare pigmented neuroectodermal locally aggressive tumors that usually occur within 1 year of life. Head and neck areas are frequently involved with maxilla being the most common site. Expansile growth and high recurrence rate are characteristics of this cancer. Though rare, radiologists and clinicians must be aware and should consider this entity when diagnosing pediatric head and neck masses. Computed tomography can be used for diagnosing and looking at the extent of the disease and predicting the operative outcome. Surgery with wide resection margin is the mainstay of treatment for these masses. Surgery followed by adjuvant chemotherapy and radiation is reserved for aggressive malignant lesions. Since it has a high recurrence rate, follow-up is done with imaging and clinical examination. Early detection and treatment of recurrence have a favorable outcome for the patients.